2002
DOI: 10.1128/mcb.22.22.7907-7918.2002
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of DNA Replication from the Polyomavirus Origin by PCAF and GCN5 Acetyltransferases: Acetylation of Large T Antigen

Abstract: The PCAF and GCN5 acetyltransferases, but not p300 or CBP, stimulate DNA replication when tethered near the polyomavirus origin. Replication stimulation by PCAF and GCN5 is blocked by mutational inactivation of their acetyltransferase domains but not by deletion of sequences that bind p300 or CBP. Acetylation of histones near the polyomavirus origin assembled into chromatin in vivo is not detectably altered by expression of these acetyltransferases. PCAF and GCN5 interact with polyomavirus large T antigen in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 121 publications
(111 reference statements)
0
22
0
Order By: Relevance
“…A similar effect is observed if the Gcn5 histone acetyltransferase (HAT) is tethered next to an origin (329). Interestingly, tethering of PCAF/ Gcn5 HAT adjacent to the polyomavirus replication origin also stimulates replication in animal cells (342). Early studies suggested that regions of the chromatin associated with MCM proteins are more susceptible to nuclease digestion, indicating that these domains may be less tightly compacted (118,262).…”
Section: Chromatin Remodelingmentioning
confidence: 80%
See 3 more Smart Citations
“…A similar effect is observed if the Gcn5 histone acetyltransferase (HAT) is tethered next to an origin (329). Interestingly, tethering of PCAF/ Gcn5 HAT adjacent to the polyomavirus replication origin also stimulates replication in animal cells (342). Early studies suggested that regions of the chromatin associated with MCM proteins are more susceptible to nuclease digestion, indicating that these domains may be less tightly compacted (118,262).…”
Section: Chromatin Remodelingmentioning
confidence: 80%
“…As described above, the histone aceyltransferase PCAF/Gcn5 is reported to stimulate replication from a viral origin by contributing to the acetylation of polyomavirus T antigen, a viral helicase similar to MCMs (342). This suggests that the interaction of MCMs with other HATs such as Hbo1 may result in MCM acetylation.…”
Section: Acetylationmentioning
confidence: 95%
See 2 more Smart Citations
“…The polyomavirus large T-Ag (PyLT) has been reported to be acetylated by PCAF and GCN5 (Xie et al, 2002). The acetylation of the PyLT is thought to have a role in stimulating DNA replication.…”
Section: Regulation Of T-ag By Acetylation T Shimazu Et Almentioning
confidence: 99%